High diversity of Trichonectria ( Hypocreales ) inhabiting Usnea in Bolivia - Javier Etayo; Valerii Darmostuk; Martin Kukwa; Adam Flakus (Plant and Fungal Systematics)
The Neotropics, particularly mountain cloud forests, are characterized by a high diversity of microfungi that inhabit lichens. However, based on our field studies, many of these microfungi remain undescribed, and their phylogenetic relationships are poorly understood. This study focuses on Bolivian lichenicolous Trichonectria inhabiting the genus Usnea ( Parmeliaceae ), a common lichen host in the tropical Andean forests. Here, we present 14 species of which eight are described as new to science: Trichonectria abortispora sp. nov., T. biglobospora sp. nov., T. boliviana sp. nov., T. citrispor a sp. nov., T. cylindrospora sp. nov., T. gigaspora sp. nov., T. microsporusneae sp. nov. and T. toensbergiana sp. nov. The five-locus phylogenetic analyses show that the anamorphic genus Cylindromonium and the teleomorphic genus Trichonectria cluster together in a well-supported clade within the order Hypocreales , but we have not yet reached a taxonomic conclusion. Phylogenetic placements of five lichenicolous species of the genus Trichonectria are reported here for the first time, including T. vinosa comb. nov.